Efficiency in health public services provision and market failure - Meza Carvajalino, Carlos Arturo (Universidad de La Salle. Revistas. Equidad & Desarrollo., 2006)
This document studies the theoretical foundations, the different controversies regarding the health service and the conceptions adopted from the hypotheses related to the market efficiency in the provision of a public service and the consequent market failures. The author thinks that when the health public service was delegated to the market in Colombia they originated failures in the competition, externalities, preference goods and services, asymmetry and redistribution, among the most relevant ones.